“I Have the Right”: Connecting the Human Body to Human Rights - Holly Hardin (WOW Stories)
Holly Hardin centers human rights for her unit on the human body for her science class, using the text "I Have the Right: An Affirmation of the United Nations Convention on the Rights of the Child" as a cornerstone for the unit as well as a text set curated to provide additional information and narratives students can relate to that also provide real world examples of topics covered in class.